Measurement properties of the Project-Level Women’s Empowerment in Agriculture Index - Yount, Kathryn M.; Cheong, Yuk Fai; Maxwell, Lauren; Heckert, Jessica; Martinez, Elena M.; Seymour, Greg (International Food Policy Research Institute, 2019)
Given the need for valid measures of women’s empowerment to monitor SDG5 and design advantages of pro-WEAI, an assessment of its measurement properties is warranted. This paper has three aims: 1) to assess in two GAAP2 projects the measurement properties of survey question (item) sets used to compute pro-WEAI indicators, 2) to offer guidance, based on study findings, for questionnaire revisions to shorten the full pro-WEAI to improve it as a measure for women’s empowerment in agricultural development programs, and 3) to make a call for a validated ‘short form’1 version of pro-WEAI and improved measures of women’s collective agency.